2019
DOI: 10.1111/ele.13400
|View full text |Cite
|
Sign up to set email alerts
|

Neighbour species richness and local structural variability modulate aboveground allocation patterns and crown morphology of individual trees

Abstract: Local neighbourhood interactions are considered a main driver for biodiversity–productivity relationships in forests. Yet, the structural responses of individual trees in species mixtures and their relation to crown complementarity remain poorly understood. Using a large‐scale forest experiment, we studied the impact of local tree species richness and structural variability on above‐ground wood volume allocation patterns and crown morphology. We applied terrestrial laser scanning to capture the three‐dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 64 publications
(93 reference statements)
5
95
1
1
Order By: Relevance
“…Next to resource partitioning, microclimate amelioration via facilitative neighbourhood interactions might act as a further mechanism by which the water demand of a focal tree growing in diverse neighbourhoods is decreased. For example, increasing tree species diversity at the local neighbourhood scale allows for more complex structured and densely packed canopies by shifts in wood volume allocation in favour of branches over time (Kunz et al, ). This, in turn, can reduce irradiance, air and soil surface temperature as well as vapour pressure deficits at the leaf surface and the evaporative demand of whole trees (Montgomery, Reich, & Palik, ), therefore improving abiotic growing conditions during drought.…”
Section: Discussionmentioning
confidence: 99%
“…Next to resource partitioning, microclimate amelioration via facilitative neighbourhood interactions might act as a further mechanism by which the water demand of a focal tree growing in diverse neighbourhoods is decreased. For example, increasing tree species diversity at the local neighbourhood scale allows for more complex structured and densely packed canopies by shifts in wood volume allocation in favour of branches over time (Kunz et al, ). This, in turn, can reduce irradiance, air and soil surface temperature as well as vapour pressure deficits at the leaf surface and the evaporative demand of whole trees (Montgomery, Reich, & Palik, ), therefore improving abiotic growing conditions during drought.…”
Section: Discussionmentioning
confidence: 99%
“…As hypothesized, we found that between sites canopy rugosity was greatest where taxonomic, particularly family, richness was high. Crown morphological divergence in more diverse forests (Benavides, Scherer‐Lorenzen, & Valladares, 2019; Kunz et al, 2019) may enhance complexity by supplying a variety of architectures, heights and forms. In our study, crown morphological redundancy may explain why family – rather than species or genus – richness was more highly correlated with canopy rugosity.…”
Section: Discussionmentioning
confidence: 99%
“…Canopy structural complexity, which describes horizontal and vertical variation in vegetation density, height or distribution, is an emergent ecosystem property that may be viewed as a product of several forest community and structural features (Ali, 2019; Ali et al, 2019; Ehbrecht, Schall, Juchheim, Ammer, & Seidel, 2016; Forrester, 2019; LaRue, Hardiman, Elliott, & Fei, 2019; Seidel, 2018; Wilkes et al, 2016). Plant taxonomic and phylogenetic diversity supports complexity by supplying interspecific genetic diversity and the related crown architectural variety required to build complex canopy structures (Figure 1a; Ali et al, 2019; Fotis et al, 2018; Jucker, Bouriaud, & Coomes, 2015; Kunz et al, 2019; Pretzsch et al, 2015; Seidel, Annighofer, et al, 2019). Leaf mass or area provides the construction materials with which to manufacture complex canopy structures (Figure 1b; Hardiman, Bohrer, Gough, Vogel, & Curtis, 2011; Pretzsch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that TLS technology can be used for detecting structural changes in single trees as well as changes in the canopy structure [30][31][32][33][34][35], there is still a limited understanding on how different kinds of forest structural changes can be quantified using TLS in boreal forest conditions. Srinivasan et al [30] used TLS data from two time points (2009 and 2012) for modeling tree biomass changes in East Texas.…”
Section: Introductionmentioning
confidence: 99%
“…The approach can be used at the local neighborhood level for revealing the extent of canopy space-filling, identifying interactions between trees, and analyzing complementary space use. Kunz et al [34] used TLS data to capture the three-dimensional structure of trees and investigate their temporal dynamics. Bi-temporal TLS data was collected between 2012 and 2016 and QSMs were then used to reconstruct tree stems and branches followed by the generation of 2D and 3D alpha-shapes for deriving additional crown shape and size parameters.…”
Section: Introductionmentioning
confidence: 99%